Characterization of cytochrome P450 isoforms involved in sequential two-step bioactivation of diclofenac to reactive p-benzoquinone imines. (24th June 2016) - den Braver, Michiel W.; den Braver-Sewradj, Shalenie P.; Vermeulen, Nico P.E.; Commandeur, Jan N.M.
Highlights: CYP3A4 and CYP2C9 are sequentially involved in the two-step formation of diclofenac-2, 5-quinone imine. Two-step diclofenac-1′, 4′-quinone imine formation involves CYP2C9 in both steps. The involvement of multiple CYPs in the sequential oxidation of DF has important implication for prediction of individual variability in exposure to p -benzoquinone imines, as CYP activity is highly variable. The results explain previous in vitro data in which DF toxicity was only apparent when multiple CYPs were expressed simultaneously. Abstract: Idiosyncratic drug-induced lever injury (IDILI) is a rare but severe side effect of diclofenac (DF). Several mechanisms have been proposed as cause of DF-induced toxicity including the formation of protein-reactive diclofenac-1′, 4′-quinone imine (DF-1′, 4′-QI) and diclofenac-2, 5-quinone imine (DF-2, 5-QI). Formation of these p -benzoquinone imines result from two-step oxidative metabolism involving aromatic hydroxylation to 4′-hydroxydiclofenac and 5-hydroxydiclofenac followed by dehydrogenation to DF-1′, 4′-QI and DF-2, 5-QI, respectively. Although the contribution of individual cytochrome P450s (CYPs) in aromatic hydroxylation of DF is well studied, the enzymes involved in the dehydrogenation reactions have been poorly characterized. The results of the present study show that both formation of 4′-hydroxydiclofenac and it subsequent bioactivation to DF-1′, 4′-QI is selectively catalyzed by CYP2C9. However, the two-step bioactivation to DF-2, 5-QI appears to be catalyzed with highest activity by two different CYPs: 5-hydroxylation of DF is predominantly catalyzed by CYP3A4, whereas its subsequent bioactivation to DF-2, 5-QI is catalyzed with 14-fold higher intrinsic clearance by CYP2C9. The fact that both CYPs involved in two-step bioactivation of DF show large interindividual variability may play a role in different susceptibility of patients to DF-induced IDILI. Furthermore, expression levels of these enzymes and protective enzymes might be important factors determining sensitivity of in vitro models for hepatotoxicity.